Application and Hazards of Nanotechnology in Drug Delivery - A Review - Gerish E1*, Mansour L2, Dardour A3, Al-Fallani E1, Saleh S4, Al-Tajoury A5, Abuderhiba KH1, Abu Senina A3 (AlQalam Journal of Medical and Applied Sciences, 2017)
General concept: Nanotechnology is a revolutionary field of micro manufacturing involving physical and chemical changes to produce nano-sized materials. The word “nano” is a Latin word meaning “dwarf”. Mathematically a nanometer is equal to one thousand millionth of a meter. Although, the initial properties of nanomaterials studied were for its physical, mechanical, electrical, magnetic, chemical and biological applications, recently, attention has been geared towards its pharmaceutical application, especially in the area of drug delivery. Over the last decades, different types of nanoparticles have been developed based on various components, including carbon, silica oxides, metal oxides, nanocrystals, lipids, polymers, dendrimers, and quantum dots, together with increasing variety of newly developed materials. These nanomaterials are capable to provide a high degree of biocompatibility before and after conjugation to biomolecules for specific function so as to translate into nanomedicines and clinical practice. Nanomaterials provide for a favorable blood half-life and physiologic behavior with minimal off-target effects, high specificity towards the target site, effective clearance from the human organism, and minimal or no toxicity to healthy tissues in living organisms. In addition, the nanosize also allows for access into the cell and various cellular compartments including the nucleus. Nanotechnology definitely promises to serve as drug delivery carrier of choice for the more challenging conventional drugs used for the treatment and management of chronic diseases such as cancer, asthma, hypertension, HIV and diabetes. This review provides an overview on the currently used systems of nanotechnology in drug delivery, applications and hazards of nanotechnology in pharmaceuticals release. Conclusion: Although for pharmaceutical use the current requirements seem to be adequate to detect most of the adverse effects of nanoparticle formulations, it can not be expected that all aspects of nanoparticle toxicology will be detected. So, probably additional more specific testing would be required.